Malice - Becker, Harold, 1928-; Neuwirth, Bebe, 1958-; Bill Pullman; Nicole Kidman; Alec Baldwin (Canada, USA Castle Rock Entertainment, 1993)
A tail about a happily married couple who would like to have children. Tracy teaches infants, Andy's a college professor. Things are never the same after she is taken to hospital and operated upon by Jed, a ""know all"" doctor.
A tale about a happily married couple who would like to have children. Tracy teaches infants, Andy's a college professor. Things are never the same after she is taken to hospital and operated upon by Jed, a ""know all"" doctor.
Aaron Sorkin
Language : English Subtitle : English
Keywords: Crime -- Mystery -- Thriller